2021
DOI: 10.3390/electronics10101155
|View full text |Cite
|
Sign up to set email alerts
|

Fast Fallback Watermark Detection Using Perceptual Hashes

Abstract: Forensic watermarking is often used to enable the tracing of digital pirates that leak copyright-protected videos. However, existing watermarking methods have a limited robustness and may be vulnerable to targeted attacks. Our previous work proposed a fallback detection method that uses secondary watermarks rather than the primary watermarks embedded by existing methods. However, the previously proposed fallback method is slow and requires access to all watermarked videos. This paper proposes to make the fallb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Note that a recompression with QP 𝑎 = 47 results in a very low-quality video. Watermark detection was performed for each attacked video, using the slow watermark detection [11], the proposed fast watermark detection using NS-DCT-DST hashes, as well as the proposed fast detection method using TIRI-DCT hashes from the state of the art [12]. The FP probability was set to 𝑃 fp = 10 −6 , corresponding to a threshold 𝑇 ≈ −4.7534.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that a recompression with QP 𝑎 = 47 results in a very low-quality video. Watermark detection was performed for each attacked video, using the slow watermark detection [11], the proposed fast watermark detection using NS-DCT-DST hashes, as well as the proposed fast detection method using TIRI-DCT hashes from the state of the art [12]. The FP probability was set to 𝑃 fp = 10 −6 , corresponding to a threshold 𝑇 ≈ −4.7534.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, this paper proposes to utilize perceptual hashes to perform fast and robust watermark detection. It has been shown that applying perceptual hashes on watermarks has merit as well [12]. However, the robustness of this fallback system decreased due to using the hashes, and the system is still non-blind.…”
Section: Introductionmentioning
confidence: 99%
“…Watermarking can be executed in a spatial domain [4,13,23,28,29] or a transform domain [3,[5][6][7][8][9][10][11][12]14,15,18,19,21,22,[24][25][26][27][30][31][32][33][34][35]. The spatial domain watermarking has high efficiency by modifying the pixels of the host images or frames directly to embed the watermark.…”
Section: Related Workmentioning
confidence: 99%
“…The spatial domain watermarking has high efficiency by modifying the pixels of the host images or frames directly to embed the watermark. In comparison, the transform domain watermarking modifies the coefficients obtained by transformation, such as the Discrete Cosine Transform (DCT) [8][9][10]18,19,21,22,24,26,30,31], Discrete Wavelet Transform (DWT) [7,11,12,14,[25][26][27]32,33], Singular Value Decomposition (SVD) [6,12,25,26], Discrete Multiwavelet Transformation (DMT) [3], Contourlet Transform [6], Dual-Tree Complex Wavelet Transform (DT CWT) [5,15,34], and so on. They possess better imperceptibility and robustness, but their computational complexity is higher than that of the spatial domain watermarking.…”
Section: Related Workmentioning
confidence: 99%
“…Two metrics are utilized to assess the robustness of our proposal: (1) true-positive rate (TPR), and (2) false-negative Rate (FNR) [34]. Equation (2) calculates true positive (TP), which reflects correctly identified embedded watermarks.…”
Section: Performance Measuresmentioning
confidence: 99%